3D Printing in the Context of Cloud Manufacturing. (April 2022) - Cui, Jin; Ren, Lei; Mai, Jingeng; Zheng, Pai; Zhang, Lin
Highlights: Two typical models of 3D printing in cloud manufacturing environment, i.e. primary 3D printing cloud model and advanced 3D printing cloud model, are presented and compared. The system architecture design of a 3D printing cloud platform based on the advanced 3D printing cloud model is proposed. A series of key enabling technologies are presented based on the proposed 3D printing cloud platform system architecture, and a prototype platform is deployed. Abstract: 3D printing has drawn tremendous attention in Industry 4.0. Nowadays, with the ever-increasing consumers' requests for 3D printing services, there lies a big challenge to eliminate the unbalanced demands and supplies of 3D printing resources in a geographically distributed environment. Cloud manufacturing, as a newly emerged service-oriented manufacturing paradigm, provides a promising way to overcome the challenge by integrating 3D printing into the cloud-based context, which may flourish the development of smart networks of virtual 3D printing cloud and also promote a novel 3D printing service business model to achieve mass customization. This paper presents a comprehensive study of 3D printing in cloud manufacturing environment. Two typical models of 3D printing, i.e. primary 3D printing cloud model and advanced 3D printing cloud model are presented and compared. The system architecture design of a 3D printing cloud platform is proposed to support the latter model. Furthermore, a series of key enabling technologies are presented based on the proposed system architecture. Finally, a prototype of 3D printing cloud platform is deployed with a case study of an aircraft engine part. The research will provide valuable theoretical and practical references to the future development of 3D printing clouds.